Ezra and Nehemiah an introduction and commentary - Kidner, Derek (Leicester, UK IVP, 1979)
Includes bibliographical references.
Keywords: Bible. O.T. Ezra -- commentaries; Bible. O.T. Nehemiah -- commentaries